Transcriptomic landscapes of ornamental plants under salt and drought stress: key genes and pathways for tolerance - Alaswad, Alaa A (Frontiers in Plant Science, 2025)
Salinity and drought are major ecological stresses that threaten the growth, appearance, and market value of ornamental plants. Transcriptomic studies have revealed the molecular basis of these responses, identifying pathways such as abscisic acid signaling, ion regulation, osmolyte accumulation, aquaporin-mediated water transport, antioxidant defense, and wax biosynthesis. Key transcription factor families (DREB/CBF, NAC, MYB, bZIP, WRKY, ERF) emerge as central regulators, acting alongside post-transcriptional and epitranscriptomic layers including alternative splicing, microRNAs, long non-coding RNAs, and m6A RNA modifications. Comparative analyses across roses, chrysanthemums, petunias, irises, and orchids reveal both conserved regulatory themes and species-specific adaptations, highlighting resilience mechanisms unique to ornamentals. This review synthesizes these insights and emphasizes their translational potential, particularly through marker-assisted selection and genome editing, to accelerate the breeding of ornamental varieties adapted to climate change.